2018
DOI: 10.3329/jcamr.v4i2.36359
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report On Cutaneous Leiomyosarcoma with Review of Literatures

Abstract: Cutaneous leiomyosarcoma represents superficial form of leiomyosarcoma which is a rare mesenchymal tumour originating from smooth muscle cells. Clinically cutaneous leiomyosarcoma can be confused with other cutaneous tumour and needs histopathology and immunohistochemistry to confirm the diagnosis. As it is an uncommon malignant neoplasm we encouraged reporting this case who presented to our hospital as an irregular nodular cutaneous lump of short duration in her right thigh. After local excision histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The occurrence of lipomas on the trunk or extremities is an uncommon event 6–8 , 13 and even rarer in chronically irritated device pockets 12 , 14 , 15 . Previous investigations have shown that lipomatous tumours at 50% represent the most common group of mesenchymal growths with a mostly good prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of lipomas on the trunk or extremities is an uncommon event 6–8 , 13 and even rarer in chronically irritated device pockets 12 , 14 , 15 . Previous investigations have shown that lipomatous tumours at 50% represent the most common group of mesenchymal growths with a mostly good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The deeper ones measured over 6 cm and were thus twice the size of the subcutaneous lipomas. In addition, the risk of transformation into a liposacroma or the also mesenchymal, highly malignant cutaneous leiomyosarcoma 13 , 15 increased with tumor size (> 5 cm) and tissue depth. 8 Another smaller study 9 was able to show that 70% of lipomas were caused by sustained tissue stress such as blunt soft tissue injuries with extensive and slowly resorbing haematomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 According to Begum and Hossain, the standard guidelines recommend performing a soft tissue ultrasound scan to confirm the mass and show the plane of the mass. 12 Ultrasonography has been found to be more sensitive compared with palpation for identifying lipohypertrophy (98% and 70%, respectively). 13 In addition, executing an immunohistochemistry (IHC) of a biopsy sample of the mass would reveal prominently actin positive, desmin positive and is CD34 negative.…”
Section: Introductionmentioning
confidence: 99%